Life after the 30-second spot : - Jaffe, Joseph (Wiley, 2005)
affe, marketing consultant and former advertising executive, issues a clarion call to abandon the old rules of marketing and wake up to new opportunites. He cites as a root problem the lack of imagination in big agencies (which may not endear him to former agency colleagues!). He offers several lists that help us understand his road map for change, such as major trends that should inspire smart marketers, including the need for 24/7/365 service to customers on their terms--and, through wireless, consumers are always connected and accessible, no matter where they are. The author presents 10 bold alternatives to traditional advertising, which include the Internet, video games that go beyond child's play, word-of-mouth advertising in which communities have the power to build brands, and reckoning with search engines, gatekeepers to online activity. In this excellent book, the author offers thought-provoking insight and advice on how to effectively serve the changing customer. Although not all readers will agree with Jaffe, they ignore him at their peril.